Existing concepts in the law of the sea: possible bases for places of refuge? - Roux, Pierre (Shipping Law Unit, 2025)
On 11 November 2002 the Bahamian registered tanker, the Prestige, laden with 77,000 tons of heavy oil en-route from Latvia to Singapore developed a 10 meter crack in the hull in heavy weather off Cape Finisterre. On the 13 th it sent out a distress signal that the hull had ruptured and oil was leaking. It was then 35 nm offshore and drifting shorewards. On the 14 th it was taken in tow by a salvage team, which succeeded in stabilising it. It requested permission to be towed into the calmer waters of a sheltered harbour to transfer its cargo to another tanker. France, the UK and nearby Spain and Portugal refused permission, fearing pollution and explosion in a confined harbour area. Under Spanish orders and shadowed by a naval frigate the Prestige was towed out to sea and then south towards Portuguese waters. Rough seas damaged it further and on the 15 th the master abandoned ship. Meanwhile, about 6,000 tons of oil escaped and were polluting the Spanish coast, fouling beaches and seabirds and closing fisheries and shellfish beds. It caused a political storm onshore and within the European Union. Portugal then dispatched a frigate to push the tugs westwards, further out to sea. On the 19 th the Prestige, buffeted by huge waves for a week, split apart and sank 145 nm off the Spanish coast near the Portuguese EEZ, causing the worst oil spill since the grounding of the Exxon Valdez in 1989. The oil spread was driven onshore polluting 290 km of Spanish coastline. If the tanker had been given shelter in a small bay the pollution could easily have been contained. It also threatened to pollute the coasts of France and Portugal. In the wake of the Prestige disaster, Spain and Portugal were blamed for exacerbating what should have been a minor oil spill by refusing to give the tanker permission to dock in a sheltered area.